Huperzia wusugongii nom. nov. (Lycopodiopsida: Huperziaceae) from West China - Xu, Xiao-Gang; Zhou, Xin-Mao; Zhang, Li-Bing (Phytotaxa, 2017)
A new name of the lycophyte genus Huperzia (Huperziaceae), H. wusugongii Li Bing Zhang, X.G. Xu & X.M. Zhou, from west China is proposed to replace the later homonym, H. rubricaulis S.K. Wu & X. Cheng [‘rubicaulis’], of H. rubricaulis (Alderwerelt van Rosenburgh) Holub.